Antioxidant responses of wheat plants under stress - Andréia Caverzan (Genetics and Molecular Biology, 2016)
Abstract Currently, food security depends on the increased production of cereals such as wheat (Triticum aestivum L.), which is an important source of calories and protein for humans. However, cells of the crop have suffered from the accumulation of reactive oxygen species (ROS), which can cause severe oxidative damage to the plants, due to environmental stresses. ROS are toxic molecules found in various subcellular compartments. The equilibrium between the production and detoxification of ROS is sustained by enzymatic and nonenzymatic antioxidants. In the present review, we offer a brief summary of antioxidant defense and hydrogen peroxide (H2O2) signaling in wheat plants. Wheat plants increase antioxidant defense mechanisms under abiotic stresses, such as drought, cold, heat, salinity and UV-B radiation, to alleviate oxidative damage. Moreover, H2O2 signaling is an important factor contributing to stress tolerance in cereals.